Motivasi Berprestasi Siswa Ditinjau dari Efikasi Diri dan Dukungan Sosial Orangtua - Kemala Fitri; Elfida, Diana; Kusnadi (Jurnal Psikologi Integratif, 2025)
Achievement motivation is the drive within an individual to achieve success with all his efforts and abilities in accordance with established standards and to be superior to others. In order for students to have achievement motivation, they need to pay attention to the factors that influence achievement motivation, both internal and external. Previous research shows the role of self-efficacy and parental social support in influencing a person's drive to succeed. Based on this, this research aims to examine the relationship between student achievement motivation in terms of self-efficacy and parental social support. Quantitative methods were used as research method. There were 243 high school/equivalent students in Kuok District who were the research samples using a purposive sampling technique. Data were collected using an adapted scale of the Motivation Achievement Inventory, the General Self-Efficacy Scale, and a modified scale of the Child and Adolescent Social Support Scale. Then non-linear regression analysis technique was used to analyze the research data. The research results showed a significant and positive relationship between self-efficacy and achievement motivation with an effective contribution of 22.5%. Then there was a significant and positive relationship between parental social support on achievement motivation and an effective contribution of 15.3%. It could be concluded that the increase in students' achievement motivation was due to an increase in students' self-efficacy. Then, on the other hand, this is also due to the increase in parental social support that students receive.   Motivasi berprestasi adalah dorongan dalam diri individu untuk mendapatkan kesuksesan dengan segenap usaha dan kemampuan sesuai dengan standar yang ditetapkan serta menjadi lebih unggul dibanding orang lain. Agar siswa memiliki motivasi berprestasi perlu memperhatikan faktor-faktor yang memengaruhi motivasi berprestasi baik internal dan eksternal. Penelitian terdahulu memperlihatkan peran efikasi diri dan dukungan sosial orangtua memengaruhi dorongan seseorang untuk sukses. Berdasarkan hal tersebut, penelitian ini bertujuan menguji hubungan motivasi berprestasi siswa ditinjau dari efikasi diri dan dukungan sosial orangtua. Metode kuantitatif digunakan sebagai metode penelitian. Terdapat 243 siswa Sekolah Menengah Atas/Sederajat di Kecamatan Kuok yang menjadi sampel penelitian dengan teknik purposive sampling. Pengumpulan data menggunakan skala adaptasi Motivation Achievement Inventory, General Self-Efficacy Scale, dan skala modifikasi the Child and Adolescent Social Support Scale kemudian dianalisis menggunakan analisis regresi non linear. Hasil penelitian menunjukan hubungan yang signifikan dan positif antara efikasi diri terhadap motivasi berprestasi dengan sumbangan efektif sebesar 22,5%, terdapat hubungan signifikan dan positif antara dukungan sosial orang tua terhadap motivasi berprestasi dengan sumbangan efektif sebesar 15,3%.  Dapat disimpulkan bahwa meningkatnya motivasi berprestasi siswa karena adanya peningkatan efikasi diri dalam diri siswa. Kemudian dilain sisi juga diakibatkan karena meningkatnya dukungan sosial orang tua yang diterima siswa.